Recruitment, adherence and attrition challenges in internet-based indicated prevention programs for eating disorders: lessons learned from a randomised controlled trial of ProYouth OZ - Ali, Kathina; Fassnacht, Daniel B.; Farrer, Louise M.; Rieger, Elizabeth; Moessner, Markus; Bauer, Stephanie; Griffiths, Kathleen M. (Journal of eating disorders, 2022)
Growing evidence supports the effectiveness of Internet-based prevention programs for eating disorders, but the adjunctive benefit of synchronous peer support has yet to be investigated. In the current study, a randomised controlled trial was conducted to evaluate the effectiveness of an indicated Internet-based prevention program (ProYouth OZ) with and without peer-to-peer support in reducing disordered eating behaviours and attitudes.